Patient Safety Culture at Rumah Sakit Mata Undaan in 2023: An HSOPSC Survey - Kartika Sari, Dyan; Nurharianti, Pradita Rani; Asih, Akas Yekti Pulih (Universitas Nahdlatul Ulama Surabaya, 2025)
The cornerstone of patient safety is a culture of safety, which can significantly reduce adverse events. According to the 2022 Hospital Accreditation Standards, hospitals are required to measure and evaluate patient safety culture annually. This research aims to assess the level of patient safety culture at Rumah Sakit Mata Undaan so it can serve as a reference for developing policies to enhance patient safety culture. This study employs a cross-sectional design and a quantitative methodology to conduct a descriptive investigation. This study includes the entire population, with a total sample size of 189 respondents, consisting of non-health workers, medical staff, and other healthcare workers. Measurement was conducted using the ten safety culture variables from the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire developed by AHRQ. The result indicate that 69.4% of respondents, on average, agreed with the patient safety culture dimensions. Among them,